Spirituality in The Workplace: Solution to Reduce Nurse Turnover Intention - Nikma Fitriasari (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
A frequent problem in hospitals is nurse turnover, which reaches 27.3% annually in Indonesia. The solution to this problem is increasing spirituality intelligence through the formation of spirituality in the workplace. Good spirituality in the workplace can increase productivity and organizational commitment, and reduce turnover. The study was conducted to determine the effect of spirituality in the workplace on nurse turnover intention. The study used a quantitative design with a cross-sectional approach. The sample used was 92 nurses who were determined by Proportionate Random Sampling. Data were processed using Partial Least Square (PLS). The PLS results showed T statistics of 8.927 with direct coefficients of -0.423. The application of spirituality in the workplace shapes nurses’ perceptions more positively towards hospitals, so that, nurse turnover intention is low.